2021
DOI: 10.3389/fpls.2021.725699
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Induces Paramylon Accumulation and Fine-Tuning of the Macro-Organization of Thylakoid Membranes in Euglena gracilis Cells

Abstract: The effects of salt stress condition on the growth, morphology, photosynthetic performance, and paramylon content were examined in the mixotrophic, unicellular, flagellate Euglena gracilis. We found that salt stress negatively influenced cell growth, accompanied by a decrease in chlorophyll (Chl) content. Circular dichroism (CD) spectroscopy revealed the changes in the macro-organization of pigment-protein complexes due to salt treatment, while the small-angle neutron scattering (SANS) investigations suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 83 publications
2
22
0
Order By: Relevance
“…Studies have shown that although salt stress might inhibit the growth of E. gracilis , it could significantly promote the accumulation of paramylon [ 17 ]. In the present study, NH 4 Cl was the only nitrogen source for the accumulation of paramylon in E. pisciformis cells under the mixotrophic mode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that although salt stress might inhibit the growth of E. gracilis , it could significantly promote the accumulation of paramylon [ 17 ]. In the present study, NH 4 Cl was the only nitrogen source for the accumulation of paramylon in E. pisciformis cells under the mixotrophic mode.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms leading to the increase in E. pisciformis AEW501 paramylon content under mixotrophic cultivation were speculated. Studies have shown that although salt stress might inhibit the growth of E. gracilis , it could significantly promote the accumulation of paramylon [ 17 ]. In the present study, although E. pisciformis cells with the supplementation of NH 4 Cl could accumulate plenty of paramylon granules, cell growth was significantly inhibited compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One example of where SANS has been used to study intact cells is in investigations of the thylakoid membranes, which are part of the photosynthetic apparatus of plants [ 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 ]. Thylakoid membranes organize into stacks, and thus they give rise to diffraction features in SANS patterns that can be resolved from the remainder of the signal of the leaf of the plant or cell that is being measured.…”
Section: Examplesmentioning
confidence: 99%
“…Thylakoid membranes organize into stacks, and thus they give rise to diffraction features in SANS patterns that can be resolved from the remainder of the signal of the leaf of the plant or cell that is being measured. SANS studies have been performed on cyanobacteria [ 257 , 259 , 260 , 263 , 264 ], diatoms [ 258 ], algae [ 261 , 267 ], and higher plants [ 262 , 265 , 266 ]. The impact of environmental stressors, such as salt [ 267 ], selenium [ 265 ] and herbicide [ 264 ], on the structure of the membranes has also been studied.…”
Section: Examplesmentioning
confidence: 99%